Establishing an empirical equation for the relationship between total suspended solids and total phosphorus concentrations in the downstream Red river water - Da, Le Nhu; Quynh, Le Thi Phuong; Binh, Phung Thi Xuan; Thuy, Duong Thi; Thu, Trinh Hoai; Hai, Nguyen Thi; Huong, Nguyen Thi Anh (Vietnam Journal of Marine Science and Technology, 2020)
Recently, the Asian rivers have faced the strong reduction of riverine total suspended solids (TSS) flux due to numerous dam/reservoir impoundment. The Red river system is a typical example of the Southeast Asian rivers that has been strongly impacted by reservoir impoundment in both China and Vietnam, especially in the recent period. It is known that the reduction in total suspended solids may lead to the decrease of some associated elements, including nutrients (N, P, Si) which may affect coastal ecosystems. In this paper, we establish the empirical relationship between total suspended solids and total phosphorus concentrations in water environment of the Red river in its downstream section from Hanoi city to the Ba Lat estuary based on the sampling campaigns conducted in the dry and wet seasons in 2017, 2018 and 2019. The results show a clear relationship with significant coefficient between total suspended solids and total phosphorus in the downstream Red river. It is expressed by a simple equation y = 0.0226x0.3867 where x and y stand for total suspended solids and total phosphorus concentrations (mg/l) respectively with the r2 value of 0.757. This equation enables a reasonable prediction of total phosphorus concentrations of the downstream Red river when the observed data of total suspended solids concentrations are available. Thus, this work opens up the way for further studies on the calculation of the total phosphorus over longer timescales using daily available total suspended solids values.